Effects of solutes on dislocation nucleation and interface sliding of bimetal semi-coherent interface. (August 2020) - Wang, C.J.; Yao, B.N.; Liu, Z.R.; Kong, X.F.; Legut, D.; Zhang, R.F.; Deng, Y.
Abstract: Misfit dislocations at bimetal interfaces play a key role in interface-induced deformation mechanism, which in turn determines the strengthening and softening at different length scales. Although a variety of interfaces have been explored to reveal distinct misfit dislocations and resultant deformation mechanisms, an ideal clean bimetal interface model without any solute atoms is generally assumed in modeling and simulations. Taking bimetal semi-coherent Cu{111}//{111}Ag interface as an illustration, we reveal that solute segregation at the interface could change the underlying mechanism of interface-facilitated dislocation nucleation and interface sliding. In contrary to the clean interface, the energy barrier is much lower for dislocation nucleation at compositionally diffused interfaces due to the appearance of more preferable nucleation sites at the boundaries of solute clusters than those around the nodes of misfit dislocations. We also find that solutes may modify the preferred slip systems via the formation of more complicated distribution of localized shearing regions. Further exploration of the solute effect on the resistance of interface sliding indicates that the solute segregation may also provide a strong barrier for the relative sliding between two constituent metals and change the pathway of sliding via the strong interaction between solute clusters and intersection nodes of misfit dislocations. Our results provide a foundation and emphasize the necessity to include the effect of solutes on the plastic deformation of bimetal interfaces in understanding the interface-dominated plasticity in a more realistic way. Graphical abstract: Image 1 Highlights: Solute effects on dislocation nucleation at Cu//Ag interface and interface sliding are revealed from atomic scale. Solutes decrease dislocation nucleation barrier by changing SFE of the crystal and the misfit dislocations at interface. The dislocation nucleation around solute clusters is more preferable than those around misfit dislocation nodes. Solutes can dramatically increase the interface sliding resistance and change the actual sliding pathway.